CONSUMER BEHAVIOR OF INTEREST AND USE OF CLOUD COMPUTING TECHNOLOGY AS SUPPORT TO BUSINESS ACTIVITIES - Purnamasari, Fitri; Subekti, Imam; Rahman, Aulia Fuad (Jurnal Aplikasi Manajemen, 2018)
The objective of this study is to assess the various factors that determine consumer behavioral intention and actual use of cloud computing as a technology considered capable of supporting business activities. The population of this research is the collegestudents in Malang. The data was collected through survey method. 153 questionnaires were distributed directly to the respondent or via an internet link. The study shows that there are several factors determining the behavior of individual’s intention and actual usage of cloud computing technology, that is the compatibility and the ease of use on cloud computing. Both factors proved to have partial mediation effect on the actual usage of cloud computing through the behavioral intention of using cloud computing.Other findings are positive effects of the usefulness of cloud computing on behavioral intention on using cloud computing, and the cloud computing user’s image on the actual usage of cloud computing. Businessmay consider cloud computing technology as well as those factors to be applied to gaining more consumers and can be used as a breakthrough to add new competitive advantage.